1992
DOI: 10.1111/j.1151-2916.1992.tb07224.x
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical Properties of Some Pb (Mg1/3Nb2/3–PbTiO3–(Ba,Sr)TiO3 Ceramics: I

Abstract: Compositional variation within the Pb(MgInNb2,3)03-PbTi03 -(Ba,Sr)Ti03 (hereafter PMN-PT-BT,ST) ternary (6.4% 5 PT% 5 14.1%, 1.25% 5 BT,ST% 5 2.5%) results in major changes in induced strain and hysteresis. For the 1.25% BT family, the increase in strain correlates with an increase in Tma,, while the dielectric loss is uncorrelated with hysteresis and strain. In addition, weakfield aging (which is not reset by application of field) shows little effect on strain and hysteresis for drive fields of > 0.2 MV/m. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Above the room temperature, PMN has a very slim polarization and strain vs. electric field (P2E) curve with a small coercive field. In addition, the dielectric loss of PMN decreases rapidly above the room temperature [8,9]. Therefore, it is expected that addition of PMN compensate the shortcomings of NBT; high coercive field and high conductivity.…”
Section: Introductionmentioning
confidence: 98%
“…Above the room temperature, PMN has a very slim polarization and strain vs. electric field (P2E) curve with a small coercive field. In addition, the dielectric loss of PMN decreases rapidly above the room temperature [8,9]. Therefore, it is expected that addition of PMN compensate the shortcomings of NBT; high coercive field and high conductivity.…”
Section: Introductionmentioning
confidence: 98%
“…It is well known that in relaxor ferroelectrics the frequency dependence of T m cannot be described by simple Arrhenius law which is to be expected for Debye relaxation process. Recent studies [8,12,[18][19][20] showed that, like in spin and structural glass, this dependence obeys the empirical Vogel-Fulcher law [21,22]:…”
Section: Resultsmentioning
confidence: 93%
“…The ferro-paraelectric phase transition (T m ) and all the related properties in these systems are characterized not by abrupt changes, but rather by gradual diffuse changes, which occur over a wide temperature range [3,4]. Among the various electrostrictive materials, Pb(Mg 1/3 Nb 2/3 )O 3 (PMN)-based materials have carried special attention because of their better dielectric and electrostrictive properties [5][6][7][8][9][10]. The dielectric relaxation in PMN-based materials has been investigated extensively, and believed that it is similar to the magnetic relaxation in spin-glass system.…”
Section: Introductionmentioning
confidence: 99%
“…The samples used were originally fabricated during the late 1980's and early 1990's. 20,21 The (1 Ϫx)Pb(Mg 1/3 Nb 2/3 )O 3 -xPbTiO 3 materials doped with BaTiO 3 or SrTiO 3 compositions ͑PMN-PT-BT, ST͒ are contained in a ternary, as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…22 were used here to allow direct comparison͒. 24 The technique developed here demonstrates how Fourier harmonic analysis of the electromechanical signal of an electroactive material can be related to the underlying physics of the response. This provides the necessary relationship to obtain the strain coefficients ͑function of applied electric field͒ of the material.…”
Section: Introductionmentioning
confidence: 99%